The Analysis of Family-Based Curriculum Toward the Implementation of Islami Value at Bani Hasyim Islamic School, Malang City - Lestari, Ika Dwi (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
Bani Hasyim Islamic Elementary School, Malang City applies a curriculum independently developed by emphasizing the implementation of the Islamic values to the students and remains guided by the 2013 curriculum. The curriculum is named a family-based curriculum which integrates the Islamic Religious Education (PAI) subjects in the thematic learning and also the implementation of Islamic values through the daily programs that are monitored by the role of teachers and parents. This research aims to examine the background of the establishment of the family-based-curriculum and its implementation at Bani Hasyim Islamic Elementary School, Malang City. The research method used a qualitative type. The data was obtained through in-depth interviews with school principals, curriculum development teams as well as teachers. The research result shows that the implementation background was risen by the inability of the current curriculum to create a complete human being. Meanwhile, the curriculum implementation is carried out through integrated and contextual.